Proses Pengembangan Inovasi Frugal Dilihat dari Perspektif Ekonomi Institusional Berparadigma Realisme Kritis - Dudi Hidayat (STI Policy and Management Journal, 2012)
Frugal Innovations that have been rapidly developing in India, have received widespread attention both in developing countries as well as in developed countries. It is perceived as offering possible solution for low-income people in the bottom of the pyramid in developing countries. Frugal innovation is a low-priced product or process innovation created in the middle of resource scarcity and institutional shortcomings. This paper investigates the rapidly growing literature on frugal innovation to answer the questions of what does frugal innovation actually mean? In what contects and how it most likely will develop? Who have been developing frugal innovation? What kind of capability requirements are needed in order to be able to create frugal innovation? And how the government can foster its development?Lierature investigation is carried out through Institutional Economic perspective based on critical realism paradigm. It particularly views the emergence of frugal innovation as a social phenomena within a socio-economic system. The social system is perceived as a structurized and stratified system in which frugal innovation is perceived as happening at the observed and experienced empirical level of the social system. To understand the emergence of frugal innovation one need to understand the structure and the mechanism at a deeper level than the empirical level. The investigation concludes that frugal innovations are specific innovations that require the existance of particular institutional arrangement and cultural environment. It requires three preconditions: the existance of enterpreneurs, technological capability and effective demand from the people at the bottom of the pyramid. This undertanding is very important for the government of developing countries if they are to foster frugal innovation development in their countries.